2-(3-phenyl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate and acrylonitrile copolymers: Synthesis, characterization, determination of monomer reactivity ratios, and investigation of their antifungal effects - Demirelli, K; Coskun, M; Dilsiz, N (John Wiley & Sons Ltd, 1999)
Some copolymers of 2-(3-phenyl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate (PCHEMA) with acrylonitrile (AN) have been prepared in the presence of 2,2'-azobisisobutyronitrile in 1,4-dioxane solvent at 60 degrees C. The copolymers have been characterized by infrared, H-1 and C-13 NMR techniques. The percentages of PCHEMA and AN in the copolymers have been established by elemental analysis. The glass transition temperatures as a function of PCHEMA (from 1 to 7) in the copolymer change from 88 to 103 degrees C. Initial decomposition temperatures as a function of PCHEMA in copolymer show a decrease from 310 to 262 degrees C. The monomer reactivity ratios of copolymerizations are calculated by using both Kelen-Tudos and Fineman-Ross equations. The antifungal effects of these copolymers have also been investigated using Saccharomyces cerevisiae. (C) 1999 Society of Chemical Industry.
Keywords: Polymerization